BEST PRACTICE PENGEMBANGAN KURIKULUM MELALUI KEARIFAN LOKAL MUANG JONG DI SD NEGERI 19 SIJUK, BELITUNG - Panji Arya Kusuma; Dhiniaty Gularso (STKIP Subang, 2026)
This study aims to describe and analyze the best practice of curriculum development through the integration of Muang Jong local wisdom at SD Negeri 19 Sijuk, Belitung. The research employed a qualitative descriptive approach with a case study design. Research subjects consisted of the principal, teachers, and students who were directly involved in the implementation of the local wisdom-based curriculum. Data were collected through in-depth interviews, participatory observations, and document analysis. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The results revealed that Muang Jong local wisdom has been integrated into the School Operational Curriculum, classroom learning activities, co-curricular programs, and the Projek Penguatan Profil Pelajar Pancasila (P5). The integration of local cultural values made learning more contextual and meaningful while contributing to the preservation of local culture. Furthermore, the implementation of the curriculum positively influenced students’ character development, particularly in fostering cooperation, responsibility, environmental awareness, cultural appreciation, and social values. Therefore, the Muang Jong-based curriculum development serves as an effective strategy for strengthening character education and preserving local cultural heritage within the implementation of the Merdeka Curriculum.